2020
DOI: 10.1002/jcph.1640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 Single Doses of Trazodone on QTc Interval in Healthy Subjects

Abstract: This study evaluated the effect of 3 doses of a trazodone hydrochloride 6% oral drops solution on the QT interval of healthy volunteers. Subjects were randomly assigned to receive a single dose of trazodone 20 mg, 60 mg, and 140 mg, moxifloxacin 400 mg, and trazodone-matched placebo in 5 periods separated by 7-day washouts, according to a double-blind, crossover study design. Subjects were monitored continuously, and triplicate ECGs were extracted from baseline (predose) until 24 hours postdose. Blood samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Trazodone, a serotonin antagonist and reuptake inhibitor, is used only in Japan and Belgium and is a prescribed antidepressant as well as hypnotic drug in Japan. Although trazodone did not significantly prolong QTc in a thorough QT/QTc study, 15 a retrospective case analysis of data from a poison center found that trazodone was associated with QT prolongation (QTc >500 ms) 16 . There have also been case reports of QT prolongation associated with trazodone overdose 17–19 .…”
Section: Discussionmentioning
confidence: 99%
“…Trazodone, a serotonin antagonist and reuptake inhibitor, is used only in Japan and Belgium and is a prescribed antidepressant as well as hypnotic drug in Japan. Although trazodone did not significantly prolong QTc in a thorough QT/QTc study, 15 a retrospective case analysis of data from a poison center found that trazodone was associated with QT prolongation (QTc >500 ms) 16 . There have also been case reports of QT prolongation associated with trazodone overdose 17–19 .…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether trazodone caused QT interval prolongation as described in humans, 8 QT intervals were measured 30 minutes before the 1st trazodone dose and 1 hour after the 4th trazodone dose. The QT interval was measured in milliseconds from the start of the Q wave to the end of the T wave where it intersects baseline, as previously described 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies looking at safety in large prescription datasets show trazodone to be similar to atypical antipsychotics and benzodiazepines in terms of fall and fracture risk in demented patients, but with a lower overall mortality risk [61,62]. The largest study of cardiac side effects of trazodone in older people found no effect on QTc and minimal effect on pulse or other ECG parameters [63,64]. Similarly, trazodone may be less likely to result in hyponatraemia than other antidepressants [65].…”
Section: Epidemiological Data From Observational Studies On Trazodone...mentioning
confidence: 99%